World Economic Situation and Prospects 2017 - United Nations Department of Economic; Social Affairs (United Nations, 2017)
The World Economic Situation and Prospects (WESP) is the definitive report of the United Nations on the state of the world economy. One of the most highly anticipated economic reports from the United Nations, it is jointly produced by the Department of Economic and Social Affairs, the United Nations Conference on Trade and Development and the five United Nations Regional Commissions.